Octreotide Treatment for Hypoglycemic Refractory Case Caused by Sulfonylureas with Impaired Renal Function - Taufiq Abdullah; Ali Haedar; Budi Soenarto (Jurnal Kedokteran Brawijaya, 2023)
Hypoglycemia is an emergency case that is caused by antidiabetic drugs from the sulfonylurea class. Prolonged and refractory hypoglycemia can increase mortality and morbidity. Renal impairment can result in recurrent hypoglycemic symptoms and require special treatment. In this study case, a 47-year-old woman with newly impaired renal function presented in a coma caused by hypoglycemia due to the use of glibenclamide (sulfonylurea drugs) that did not respond to standard hypoglycemic treatment. Treatment of refractory hypoglycemia is a challenge in itself. Octreotide may be considered in cases of refractory hypoglycemia that does not respond to standard glucose treatment, where in this case refractory hypoglycemia is caused by accumulating sulfonylurea because of impaired renal function.